The elements of Java style - Vermeulen, Al (SIGS reference library series, 2000)
The Elements of Java Style, written by renowned author Scott Ambler, Rogue Wave Software Vice President Alan Vermeulen, and a team of programmers from Rogue Wave, is for anyone who writes Java code. While there are many books that explain the syntax and basic use of Java, this book, first published in 2000, explains not just what you can do with the syntax, but what you ought to do. Just as Strunk and White's The Elements of Style provides rules of usage for the English language, this book provides a set of rules for Java practitioners to follow. While illustrating these rules with parallel examples of correct and incorrect usage, the book provides a collection of standards, conventions, and guidelines for writing solid Java code which will be easy to understand, maintain, and enhance. Anyone who writes Java code or plans to should have this book next to their computer.